CLINICAL STUDY ON THE EFFICACY OF THE DEVICE FOR ELECTROSTIMULATION WITH BIO-CONTROL IN REHABILITATION OF PATIENTS WITH MOTOR DEFICIENCY SUFFERED FROM CEREBRAL STROKE - Dyachuk, D.D.; Cherniy, T.V.; Lytvyn, O.V.; Kuryk, O.G. (World of Medicine and Biology, 2020)
Vascular diseases of the brain nervous system are one of the main problems in the modern and, as predictions show, future medicine. At present, great importance in the processes of rehabilitation after a stroke is attached to neuroplasticity of the brain. This approach is implemented in a new class of TRENAR® electronic devices for biologically adequate movements control. The purpose of the study was to assess the functional capabilities of the TRENAR-01® software device in the restoration of voluntary movements in patients with impaired central motor neuron function due to the past acute cerebrovascular event. Clinical neurological examination and treatment of 30 cerebral stroke patients were carried out. 15 electrical stimulation procedures were performed with the TRENAR-01® device. After treatment in the group of patients with acute cerebral circulatory disturbance (23 patients) no effect on the motor deficiency regression was only observed in one case; in patients with long-term consequences of cerebral circulatory disorders (7 patients) there was a positive tendency in motor deficiency reducing. The efficacy of training the damaged limb movements according to the program, proceeding from voluntary reductions of symmetrical healthy muscles in paralyzed patients is reliably proved (p